Catalyst for synthesis of alkylene carbonate and preparation method thereof

By supporting magnetic inorganic compounds on the functionalized chloromethyl resin matrix, a magnetic separation composite polymer organic catalysis system is formed, and the existing problems of low catalyst activity and difficulty in separation are solved, and efficient alkylene carbonate synthesis and reusable catalysts are achieved.

CN119869612AActive Publication Date: 2025-04-25CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202311384688.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-24
Publication Date
2025-04-25
Estimated Expiration
2043-10-24

AI Technical Summary

Technical Problem

Existing catalysts are low in activity and difficult to separate during the synthesis of alkylene carbonate, resulting in severe decomposition of the product.

Method used

A magnetically separated composite polymer organic catalytic system is formed by mixing the metal salt and the active central compound with the organic polymer matrix using a catalyst supported by a magnetic inorganic compound on the functionalized chloromethyl resin matrix.

Benefits of technology

The activity and selectivity of the catalyst are improved, and the reusability of the catalyst can be achieved by the magnetic properties, avoiding the decomposition of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869612A_ABST
    Figure CN119869612A_ABST
Patent Text Reader

Abstract

The invention discloses a catalyst for synthesizing cyclic alkylene carbonate, a preparation method of the catalyst and a method for preparing the alkylene carbonate through reaction of an epoxy compound and carbon dioxide. The catalyst comprises a magnetic inorganic compound and an organic polymer matrix, wherein the organic polymer matrix is a functionalized chloromethyl resin matrix. The catalyst can be used in industrial production of alkylene carbonate, and has the characteristics of high catalyst activity, high selectivity, reusability and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalysts, in particular to a catalyst for preparing alkylene carbonate by addition reaction of epoxy compounds and carbon dioxide and a preparation method thereof, as well as a method for preparing alkylene carbonate by reaction of epoxy compounds and carbon dioxide. Background Art

[0002] Alkylene carbonates such as ethylene carbonate and propylene carbonate are widely used organic chemical raw materials and are widely used as solvents and diluents in industry. Ethylene carbonate can be used as a solvent in textiles, printing, polymer synthesis and electrochemistry, and can also be used as a raw material for cosmetics and drugs and an intermediate for the corresponding diols.

[0003] Industrially, alkylene carbonate is generally prepared by reacting carbon dioxide with the corresponding alkylene oxide in the presence of a catalyst. Many catalysts have been found to have a catalytic effect on this reaction, such as transition metal complexes, main group element complexes, quaternary ammonium salts, quaternary phosphonium salts and alkali metal salts, ionic liquids, supercritical carbon dioxide and other catalytic systems.

[0004] Kim et al. studied the effect of homogeneous catalytic systems such as zinc halide, 1-alkyl-3-methyl-imidazolium halide and phosphine-containing ligands on the reaction (Angew. Chem. Int. Ed. 39 (2000) 4096-4098, Chem. Eur. J. 9 (2003) 678-686, J. Catal. 232 (2005) 80-84). After the reaction, the homogeneous catalyst needs to be separated from the product, and separation of the product from the homogeneous catalyst by distillation can cause severe decomposition of alkylene carbonate. Summary of the invention

[0005] In order to solve the problems of low catalyst activity and difficulty in separation in the above prior art, the present invention provides a catalyst for synthesizing alkylene carbonate and a preparation method thereof, as well as a method for preparing alkylene carbonate by reacting an epoxy compound with carbon dioxide.

[0006] One of the purposes of the present invention is to provide a catalyst for the synthesis of alkylene carbonate, comprising a magnetic inorganic compound and an organic polymer matrix, wherein the organic polymer matrix is ​​a functionalized chloromethyl resin matrix, and the magnetic inorganic compound is supported on the organic polymer matrix.

[0007] According to a preferred embodiment of the present invention, the magnetic inorganic compound is a magnetic metal oxide. Preferably, the magnetic metal oxide is at least one of nickel oxide, iron oxide and cobalt oxide.

[0008] According to a preferred embodiment of the present invention, the functionalized chloromethyl resin matrix is ​​a chloromethyl resin functionalized with an active center compound containing nitrogen and / or sulfur and / or phosphorus.

[0009] The chloromethyl resin is at least one of chloromethyl-modified polystyrene resin, chloromethyl-modified polyethylene resin, chloromethyl-modified carboxylic acid-based resin and chloromethyl-modified phenolic-based resin.

[0010] The active center compound is selected from at least one of amine, pyridine, imidazole, quinoline, pyrrole, indole, carbazole, thiazole, thiophene, phosphazene, thiol, thioether, phosphorus trichloride and triphenylphosphine.

[0011] According to a preferred embodiment of the present invention, the mass content of the magnetic inorganic compound in the catalyst is 0.5-20%, preferably 1-15%, for example, it can be 0.5%, 1%, 2%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, etc.

[0012] According to a preferred embodiment of the present invention, the mass content of nitrogen and / or sulfur and / or phosphorus in the active center compound in the catalyst is 2-20%, preferably 3-15%, more preferably 3-10%, for example, it can be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 12%, 15%, 18%, 20% and the like.

[0013] The second object of the present invention is to provide a method for preparing the catalyst for the synthesis of alkylene carbonate, comprising the following steps:

[0014] (1) dispersing a metal salt in a solvent;

[0015] (2) dissolving the active center compound in a solvent;

[0016] (3) mixing the solutions obtained in steps (1) and (2), adding an organic polymer matrix, and heating the mixture to react;

[0017] (4) filtering, washing and drying to obtain the catalyst.

[0018] According to a preferred embodiment of the present invention, in steps (1) and (2), the solvent is at least one of alcohol and glucose, wherein the alcohol is preferably at least one of methanol, ethanol, ethylene glycol, propanol, propylene glycol, glycerol, butanol and pentanol.

[0019] According to a preferred embodiment of the present invention, the metal salt is at least one of sulfate, nitrate or halide of iron, cobalt or nickel.

[0020] According to a preferred embodiment of the present invention, the organic polymer matrix is ​​a chloromethyl resin, more preferably at least one of a chloromethyl-modified polystyrene resin, a chloromethyl-modified polyethylene resin, a chloromethyl-modified carboxylic acid-based resin, and a chloromethyl-modified phenolic-based resin.

[0021] According to a preferred embodiment of the present invention, the organic polymer matrix is ​​spherical.

[0022] According to a preferred embodiment of the present invention, the chlorine content in the organic polymer matrix is ​​greater than 5 wt%, preferably 7 to 25 wt%.

[0023] According to a preferred embodiment of the present invention, the particle size of the organic polymer matrix is ​​0.1 to 3 mm, preferably 0.3 to 2 mm.

[0024] According to a preferred embodiment of the present invention, the active center compound is selected from at least one of amines, pyridine, imidazole, quinoline, pyrrole, indole, carbazole, thiazole, thiophene, phosphazene, thiol, thioether, and phosphorus trichloride.

[0025] According to a preferred embodiment of the present invention, the mass ratio of the metal salt to the organic polymer matrix is ​​0.001-0.5, preferably 0.01-0.2, for example, it can be 0.001, 0.005, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, etc.

[0026] According to a preferred embodiment of the present invention, the mass ratio of the active center compound to the organic polymer matrix is ​​0.1-1, preferably 0.2-1, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, etc.

[0027] According to a preferred embodiment of the present invention, in step (3), the reaction temperature is 30 to 200° C., the reaction heating rate is 1 to 20° C. / min, and the reaction time is 1 to 24 h.

[0028] According to a more preferred embodiment of the present invention, in step (3), the reaction temperature is 40 to 180° C., the reaction heating rate is 2 to 15° C. / min, and the reaction time is 2 to 20 h.

[0029] Specifically, in step (3), the reaction temperature may be 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, etc.

[0030] Specifically, in step (3), the reaction heating rate may be 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, 11°C / min, 12°C / min, 13°C / min, 14°C / min, 15°C / min, 16°C / min, 17°C / min, 18°C / min, 19°C / min, 20°C / min, etc.

[0031] According to a preferred embodiment of the present invention, in step (4), the drying temperature is 70 to 150° C., and the drying time is 2 to 48 hours.

[0032] According to a more preferred embodiment of the present invention, in step (4), the drying temperature is 90 to 130° C., and the drying time is 4 to 36 hours.

[0033] The third object of the present invention is to provide a method for preparing alkylene carbonate by reacting an epoxy compound with carbon dioxide, comprising reacting the epoxy compound and carbon dioxide as raw materials in the presence of the above-mentioned catalyst.

[0034] According to a preferred embodiment of the present invention, the epoxy compound is an alkylene oxide, preferably at least one of ethylene oxide, propylene oxide, butylene oxide and epichlorohydrin.

[0035] According to a preferred embodiment of the present invention, the mass ratio of the catalyst to the epoxy compound is (0.001-0.5):1, preferably (0.05-0.3):1.

[0036] According to a preferred embodiment of the present invention, the reaction temperature is 60-180° C., and the reaction pressure is 0.1-10.0 MPa.

[0037] According to a more preferred embodiment of the present invention, the reaction temperature is 80-170° C., and the reaction pressure is 1-8 MPa.

[0038] The catalyst described in the present invention is a magnetic separation composite polymer organic catalytic system. The technical solution effectively solves the problems of low activity and easy loss of the catalytic system for synthesizing alkylene carbonate, can be used in the industrial production of alkylene carbonate, and has the characteristics of high catalyst activity, high selectivity, and reusability. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 is the XRD pattern of catalyst S1.

[0040] Figure 2 is the XPS spectrum of catalyst S1. DETAILED DESCRIPTION

[0041] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the contents of the present invention still fall within the scope of protection of the present invention.

[0042] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0043] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.

[0044] In the present invention, the chlorine content is measured by collecting the combustion components after the resin is burned, collecting the combustion components with sodium hydroxide solution and then measuring them with ion chromatography; the phosphorus content is measured with an element analyzer; and the metal oxide is measured with an inductively coupled plasma method.

[0045] [Example 1]

[0046] 8.7 g of ferric nitrate was dispersed in 100 ml of glycerol, and 50 g of triphenylphosphine was dissolved in 100 ml of glycerol. The two solutions were mixed and transferred into a 500 ml three-necked flask. 50 g of chloromethylstyrene resin (spherical, 50-70 mesh, chlorine content 15 wt%) was added. The speed was 500 rpm, and the temperature was increased to 160°C at a heating rate of 2°C / min. After reacting for 12 hours, the catalyst was separated after cooling, washed with deionized water, and dried at 100°C overnight to obtain catalyst S1. The phosphorus content was 5.1%, and the iron oxide content was 3.6%. The XRD and XPS of the obtained product are shown in the attached figure. Figure 1 and 2 As shown, it can be seen that the obtained iron oxide phase is ferroferric oxide.

[0047] [Example 2]

[0048] Disperse 4.35g of ferric nitrate in 100ml of glycerol, dissolve 50g of triphenylphosphine in 100ml of glycerol, mix the two solutions and transfer them into a 500ml three-necked flask, add 50g of chloromethylstyrene resin (spherical, 50-70 mesh, chlorine content 15wt%), rotate at 500 rpm, heat to 160°C at a heating rate of 2°C / min, react for 12h, cool and separate, wash with deionized water, and dry at 100°C overnight to obtain catalyst S2, wherein the phosphorus content is 5.3% and the iron oxide content is 1.7%.

[0049] [Example 3]

[0050] 2.18 g of ferric nitrate was dispersed in 100 ml of glycerol, and 30 g of triphenylphosphine was dissolved in 100 ml of glycerol. The two solutions were mixed and transferred into a 500 ml three-necked flask, 50 g of chloromethylstyrene resin (spherical, 50-70 mesh, chlorine content 15 wt%) was added, the speed was 500 rpm, the temperature was increased to 160° C. at a heating rate of 5° C. / min, the reaction was continued for 12 hours, the mixture was cooled and separated, washed with deionized water, and dried at 100° C. overnight to obtain catalyst S3, wherein the phosphorus content was 4.8%, and the iron oxide content was 1.2%.

[0051] [Example 4]

[0052] Disperse 17g of ferric nitrate in 100ml of glycerol, dissolve 20g of triphenylphosphine in 100ml of glycerol, mix the two solutions and transfer them into a 500ml three-necked flask, add 50g of chloromethylstyrene resin (spherical, 50-70 mesh, chlorine content 15wt%), rotate at 500 rpm, heat to 160°C at a heating rate of 10°C / min, react for 12h, cool and separate, wash with deionized water, and dry at 100°C overnight to obtain catalyst S4, wherein the phosphorus content is 4.2% and the iron oxide content is 9.8%.

[0053] [Example 5]

[0054] Disperse 10g of nickel nitrate in 100ml of glycerol, dissolve 50g of triphenylphosphine in 100ml of glycerol, mix the two solutions and transfer them into a 500ml three-necked flask, add 50g of chloromethylstyrene resin (spherical, 50-70 mesh, chlorine content 15wt%), rotate at 500 rpm, heat to 160°C at a heating rate of 5°C / min, react for 12h, cool and separate, wash with deionized water, and dry at 100°C overnight to obtain catalyst S5, wherein the phosphorus content is 5.1% and the nickel oxide content is 3.9%.

[0055] [Example 6]

[0056] 5 g of cobalt nitrate tetrahydrate was dispersed in 100 ml of glycerol, and 50 g of triphenylphosphine was dissolved in 100 ml of glycerol. The two solutions were mixed and transferred into a 500 ml three-necked flask, 50 g of chloromethylstyrene resin (spherical, 50-70 mesh, chlorine content 15 wt%) was added, the speed was 500 rpm, the temperature was increased to 160° C. at a heating rate of 10° C. / min, the reaction was continued for 12 hours, the mixture was cooled and separated, washed with deionized water, and dried at 100° C. overnight to obtain catalyst S6, wherein the phosphorus content was 5.4%, and the cobalt tetroxide content was 4.7%.

[0057] [Example 7]

[0058] 8.7 g of ferric nitrate was dispersed in 100 ml of glycerol, and 50 g of imidazole was dissolved in 100 ml of glycerol. The two solutions were mixed and transferred into a 500 ml three-necked flask, 50 g of chloromethylstyrene resin (spherical, 50-70 mesh, chlorine content 15 wt%) was added, the speed was 500 rpm, the temperature was increased to 160° C. at a heating rate of 2° C. / min, the reaction was continued for 12 hours, the mixture was cooled and separated, washed with deionized water, and dried at 100° C. overnight to obtain catalyst S7, wherein the nitrogen content was 8.1%, and the iron oxide content was 5.2%.

[0059] [Comparative Example 1]

[0060] Disperse 8.7 g of ferric nitrate in 200 ml of propylene glycol, transfer the solution into a 500 ml three-necked flask, add 50 g of chloromethylstyrene resin (spherical, 50-70 mesh, chlorine content 15 wt%), rotate at 500 rpm, heat to 160° C. at a heating rate of 2° C. / min, react for 12 h, cool and separate, wash with deionized water, and dry at 100° C. overnight to obtain catalyst C1, in which the iron oxide content is 2.9%.

[0061] [Comparative Example 2]

[0062] Dissolve 50 g of triphenylphosphine in 200 ml of propylene glycol, transfer the solution into a 500 ml three-necked flask, add 50 g of chloromethylstyrene resin (spherical, 50-70 mesh, chlorine content 15 wt%), rotate at 500 rpm, heat to 160° C. at a heating rate of 2° C. / min, react for 12 h, cool and separate, wash with deionized water, and dry at 100° C. overnight to obtain catalyst C2, in which the phosphorus content is 5%.

[0063] [Comparative Example 3]

[0064] 8.7 g of ferric nitrate was dispersed in 100 ml of glycerol, and 50 g of triphenylphosphine was dissolved in 100 ml of glycerol. The two solutions were mixed and transferred into a 500 ml three-necked flask. 50 g of chloromethylstyrene resin (spherical, 50-70 mesh, chlorine content 15 wt%) was added. The rotation speed was 500 rpm and the temperature was increased to 160° C. at a heating rate of 50° C. / min. After reacting for 12 hours, the mixture was cooled and separated. After washing with deionized water, the mixture was dried at 100° C. overnight to obtain catalyst C3, which had a phosphorus content of 1.8% and an iron oxide content of 7.8%.

[0065] [Example 8]

[0066] The catalyst sample S1 prepared as above was used for the reaction of ethylene oxide and carbon dioxide under the following conditions: under the protection of inert gas, 35.0 g of ethylene oxide and 2 g of catalyst were added into a 200 ml autoclave, filled with 1.0 MPa CO2, heated to 120°C, and then filled with CO2, maintaining the reaction pressure at 2.0 MPa. After reacting for 2 hours, a liquid sample was taken and analyzed on a chromatogram, obtaining an ethylene oxide conversion of 99.8% and an ethylene carbonate selectivity of 99.9%.

[0067] [Example 9]

[0068] The catalyst sample S2 prepared as above was used for the reaction of ethylene oxide and carbon dioxide under the following conditions: under the protection of inert gas, 35.0 g of ethylene oxide and 2 g of catalyst were added into a 200 ml autoclave, filled with 1.0 MPa CO2, heated to 130°C, and then filled with CO2, maintaining the reaction pressure at 5.0 MPa. After reacting for 3 hours, a liquid sample was taken and analyzed on a chromatogram, obtaining an ethylene oxide conversion rate of 99.6% and an ethylene carbonate selectivity of 99.9%.

[0069] [Example 10]

[0070] The catalyst sample S3 prepared as above was used for the reaction of ethylene oxide and carbon dioxide under the following conditions: under the protection of inert gas, 35.0 g of ethylene oxide and 2 g of catalyst were added into a 200 ml autoclave, filled with 1.0 MPa CO2, heated to 120°C, and then filled with CO2, maintaining the reaction pressure at 2.0 MPa. After reacting for 2 hours, a liquid sample was taken and analyzed on a chromatogram, obtaining an ethylene oxide conversion of 99.7% and an ethylene carbonate selectivity of 99.9%.

[0071] [Example 11]

[0072] The catalyst sample S4 prepared as above was used for the reaction of ethylene oxide and carbon dioxide under the following conditions: under the protection of inert gas, 35.0 g of ethylene oxide and 2 g of catalyst were added into a 200 ml autoclave, filled with 1.0 MPa CO2, heated to 150°C, and then filled with CO2, maintaining the reaction pressure at 7.0 MPa. After reacting for 6 hours, a liquid sample was taken and analyzed on a chromatogram, and an ethylene oxide conversion rate of 99.5% and an ethylene carbonate selectivity of 99.9% were obtained.

[0073] [Example 12]

[0074] The catalyst sample S5 prepared as above was used for the reaction of ethylene oxide and carbon dioxide under the following conditions: under the protection of inert gas, 35.0 g of ethylene oxide and 2 g of catalyst were added into a 200 ml autoclave, filled with 1.0 MPa CO2, heated to 130°C, and then filled with CO2, maintaining the reaction pressure at 2.0 MPa. After reacting for 4 hours, a liquid sample was taken for chromatographic analysis, and an ethylene oxide conversion rate of 99.7% and an ethylene carbonate selectivity of 99.9% were obtained.

[0075] [Example 13]

[0076] The catalyst sample S6 prepared as above was used for the reaction of ethylene oxide and carbon dioxide under the following conditions: under the protection of inert gas, 35.0 g of ethylene oxide and 4 g of catalyst were added into a 200 ml autoclave, filled with 1.0 MPa CO2, heated to 150°C, and then filled with CO2, maintaining the reaction pressure at 7.0 MPa. After reacting for 6 hours, a liquid sample was taken and analyzed on a chromatogram, obtaining an ethylene oxide conversion of 99.8% and an ethylene carbonate selectivity of 99.9%.

[0077] [Example 14]

[0078] The catalyst sample S7 prepared as above was used for the reaction of ethylene oxide and carbon dioxide under the following conditions: under the protection of inert gas, 35.0 g of ethylene oxide and 4 g of catalyst were added into a 200 ml autoclave, filled with 1.0 MPa CO2, heated to 150°C, and then filled with CO2, maintaining the reaction pressure at 7.0 MPa. After reacting for 6 hours, a liquid sample was taken and analyzed on a chromatogram, obtaining an ethylene oxide conversion of 99.5% and an ethylene carbonate selectivity of 99.9%.

[0079] [Comparative Example 4]

[0080] The catalyst sample C1 prepared as above was used for the reaction of ethylene oxide and carbon dioxide under the following conditions: under the protection of inert gas, 35.0 g of ethylene oxide and 2 g of catalyst were added to a 200 ml autoclave, filled with 1.0 MPa CO2, heated to 120°C, and then filled with CO2, maintaining the reaction pressure at 2.0 MPa. After reacting for 2 hours, a liquid sample was taken and analyzed on a chromatogram, obtaining an ethylene oxide conversion of 5.5% and an ethylene carbonate selectivity of 99.8%.

[0081] [Comparative Example 5]

[0082] The catalyst sample C2 prepared above was used for the reaction of ethylene oxide and carbon dioxide under the following conditions: under the protection of inert gas, 35.0 g of ethylene oxide and 2 g of catalyst were added to a 200 ml autoclave, filled with 1.0 MPa CO2, heated to 120°C, and then filled with CO2, maintaining the reaction pressure at 2.0 MPa. After reacting for 2 hours, a liquid sample was taken and analyzed on a chromatogram, obtaining an ethylene oxide conversion of 84.5% and an ethylene carbonate selectivity of 99.9%.

[0083] [Comparative Example 6]

[0084] The catalyst sample C3 prepared as above was used for the reaction of ethylene oxide and carbon dioxide under the following conditions: under the protection of inert gas, 35.0 g of ethylene oxide and 2 g of catalyst were added into a 200 ml autoclave, filled with 1.0 MPa CO2, heated to 120°C, and then filled with CO2, maintaining the reaction pressure at 3.0 MPa. After reacting for 2 hours, a liquid sample was taken and analyzed on a chromatogram, obtaining an ethylene oxide conversion of 35.6% and an ethylene carbonate selectivity of 99.8%.

[0085] [Example 15]

[0086] The catalyst sample S1 prepared above was used for the reaction of ethylene oxide and carbon dioxide under the following conditions: under the protection of inert gas, 35.0 g of ethylene oxide and 2 g of catalyst were added to a 200 ml autoclave, filled with 1.0 MPa CO2, heated to 120°C, and then filled with CO2, maintaining the reaction pressure at 3.0 MPa. After reacting for 2 hours, a liquid sample was taken for chromatographic analysis. The reacted catalyst was recovered by magnetic filtration and reused 5 times under the above conditions to obtain an ethylene oxide conversion rate of 99.7% and an ethylene carbonate selectivity of 99.8%.

Claims

1. A catalyst for the synthesis of alkylene carbonate, comprising a magnetic inorganic compound and an organic polymer matrix, wherein the organic polymer matrix is ​​a functionalized chloromethyl resin matrix.

2. The catalyst according to claim 1, characterized in that: The magnetic inorganic compound is a magnetic metal oxide, preferably, the magnetic metal oxide is at least one of nickel oxide, iron oxide and cobalt oxide; and / or, The functionalized chloromethyl resin matrix is ​​a chloromethyl resin functionalized with an active center compound containing nitrogen and / or sulfur and / or phosphorus. Preferably, the chloromethyl resin is at least one of a chloromethyl-modified polystyrene resin, a chloromethyl-modified polyethylene resin, a chloromethyl-modified carboxylic acid-based resin, and a chloromethyl-modified phenolic resin; the active center compound is selected from at least one of amines, pyridine, imidazole, quinoline, pyrrole, indole, carbazole, thiazole, thiophene, phosphazene, thiol, thioether, phosphorus trichloride, and triphenylphosphine.

3. The catalyst according to claim 2, characterized in that: The mass content of the magnetic inorganic compound in the catalyst is 0.5 to 20%, preferably 1 to 15%; and / or, The mass content of nitrogen and / or sulfur and / or phosphorus in the active center compound in the catalyst is 2-20%, preferably 3-15%, and more preferably 3-10%.

4. A method for preparing a catalyst for the synthesis of alkylene carbonate according to any one of claims 1 to 3, comprising the following steps: (1) dispersing a metal salt in a solvent; (2) dissolving the active center compound in a solvent; (3) mixing the solutions obtained in steps (1) and (2), adding an organic polymer matrix, and heating the mixture to react; (4) filtering, washing and drying to obtain the catalyst.

5. The preparation method according to claim 4, characterized in that: In steps (1) and (2), the solvent is at least one of alcohol and glucose, and the alcohol is preferably at least one of methanol, ethanol, ethylene glycol, propanol, propylene glycol, glycerol, butanol, and pentanol; and / or, The metal salt is at least one of sulfate, nitrate or halide of iron, cobalt or nickel; and / or, The organic polymer matrix is ​​a chloromethyl resin; and / or, The organic polymer matrix is ​​spherical; and / or, The chlorine content in the organic polymer matrix is ​​greater than 5wt%, preferably 7-25wt%; and / or, The particle size of the organic polymer matrix is ​​0.1 to 3 mm, preferably 0.3 to 2 mm.

6. The preparation method according to claim 4, characterized in that: The mass ratio of the metal salt to the organic polymer matrix is ​​0.001 to 0.5, preferably 0.01 to 0.2; and / or, The mass ratio of the active center compound to the organic polymer matrix is ​​0.1-1, preferably 0.2-1.

7. The preparation method according to claim 4, characterized in that: In step (3), the reaction temperature is 30-200°C, the reaction heating rate is 1-20°C / min, and the reaction time is 1-24h. Preferably, the reaction temperature is 40-180°C, the reaction heating rate is 2-15°C / min, and the reaction time is 2-20h; and / or, In step (4), the drying temperature is 70-150° C., and the drying time is 2-48 hours. Preferably, the drying temperature is 90-130° C., and the drying time is 4-36 hours.

8. A method for preparing alkylene carbonate by reacting an epoxy compound with carbon dioxide, comprising reacting an epoxy compound and carbon dioxide as raw materials in the presence of the catalyst according to any one of claims 1 to 3 or the catalyst obtained by the preparation method according to any one of claims 4 to 7.

9. The method according to claim 8, characterized in that: The epoxy compound is an alkylene oxide, preferably at least one of ethylene oxide, propylene oxide, butylene oxide and epichlorohydrin; and / or, The mass ratio of the catalyst to the epoxy compound is (0.001-0.5):1, preferably (0.05-0.3):

1.

10. The method according to claim 8, characterized in that: The reaction temperature is 60-180° C., and the reaction pressure is 0.1-10 MPa; preferably, the reaction temperature is 80-170° C., and the reaction pressure is 1-8 MPa.

Citation Information

Patent Citations

  • Magnetic solid acid catalyst, preparation method and application tehreof

    CN101757949A

  • Method for preparing ethylene carbonate

    CN105085466A

  • Method for synthesizing dimethyl carbonate and ethylene glycol by catalyzing transesterification through load type ion liquid

    CN105237336A

  • Heterogeneous catalyst and method and reaction device for synthesizing cyclocarbonate using same

    CN107715912A

  • Heterogeneous catalyst and method for preparing cyclocarbonate using same

    CN107715918A